Art Dealer Networks in the Third Reich and in the Postwar Period. (July 2017) - Petropoulos, Jonathan
This article discusses art dealers who trafficked in looted art during the Third Reich and how they re-established networks and continued their trade in the postwar period. I argue that these dealers worked within a series of overlapping networks. A primary network was centered in Munich, with dealers such as Dr. Bruno Lohse (Göring's art agent in Paris during the war); Maria Almas Dietrich, Karl Haberstock, Walter Andreas Hofer, and Adolf Wüster. These individuals worked closely with colleagues in Austria, Switzerland, and Liechtenstein (states contiguous with Bavaria) in the postwar years. Many of the individuals in outer appendages of the networks had not been complicit in the Nazis' plundering program, yet they trafficked in looted works and formed dealer networks that extended to Paris, London, and New York. Both the recently discovered Gurlitt cache – over 1400 pictures located in Munich, Salzburg, and Kornwestheim – and the annotated Weinmüller auction catalogues help illuminate aspects of these networks. Art dealers played a key role in the looting operations during the Third Reich and in the transfer of non-restituted objects in the postwar period. The current generation of the profession may be the key to advancing our understanding of a still incomplete history.